The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1983
DOI: 10.1111/j.1468-5957.1983.tb00456.x
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Financial Management Techniques Currently Employed by Large U.S. Corporations

Abstract: Economic conditions have placed increased importance upon rigorous financial analysis. In order to determine which analytical techniques are currently emp loyed by management, a questionnaire was sent to each fm on the May 1980, FORTUNE 500 list. The researchsought to establish a profile of the respondents' organizational structure and to identify the primary procedures used in risk assessment, working capital management, capital budgeting, and operations research modeling. The results do suggest a basic profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
2

Year Published

1990
1990
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(52 citation statements)
references
References 22 publications
2
48
0
2
Order By: Relevance
“…Stanley & Block have also found out that 65 percent of respondents have chosen IRR as their primary technique for project evaluation (Stanley, Block 1984). The results of research conducted by Moore & Reichert revealed that 86 percent of US Fortune 500 firms as primary method use some type of discounted cash flow analysis (Moore, Reichert 1983). Other researches of large firms revealed similar results (for example, Trahan, Gitman 1995;Bierman 1993;Bruner et al 1998 and others).…”
Section: Studies On Behavioural Corporate Financesupporting
confidence: 70%
See 1 more Smart Citation
“…Stanley & Block have also found out that 65 percent of respondents have chosen IRR as their primary technique for project evaluation (Stanley, Block 1984). The results of research conducted by Moore & Reichert revealed that 86 percent of US Fortune 500 firms as primary method use some type of discounted cash flow analysis (Moore, Reichert 1983). Other researches of large firms revealed similar results (for example, Trahan, Gitman 1995;Bierman 1993;Bruner et al 1998 and others).…”
Section: Studies On Behavioural Corporate Financesupporting
confidence: 70%
“…Other researches of large firms revealed similar results (for example, Trahan, Gitman 1995;Bierman 1993;Bruner et al 1998 and others). Moore, Reichert (1983) interalia stated that volatility of economic conditions led to increased importance of rigorous financial analysis in firms -financial executives actively use financial techniques in financial decision making process; least since 1980's relatively sophisticated capital budgeting procedures were accepted across most industries (US case), and many firms supported their decision making with a "package" of formal tools. Trahan, Gitman (1995) surveyed CFO's (Chief Executive Officers) of Fortune 500 and Forbes 200 best small companies and found out that most of respondents appear to have little interest in the current state of academic research in corporate finance and are not minded to use professionals or professors consultations, both paid or unpaid; however they do express a desire to know more about various financial decision methods.…”
Section: Studies On Behavioural Corporate Financementioning
confidence: 99%
“…Competition. Organizations in regulated industries are operating in expected product markets and gain resources to use similar prediction techniques (Doeringer et al, 1968;Fiorito et al, 1985;Moore and Reichert, 1983;Vatter, 1967). Empirical studies have shown that the accuracy of forecasting techniques varies (Mahmoud, 1984).…”
Section: Manpower Planning In Practicementioning
confidence: 99%
“…The results also indicate a slightly positive correlation between the level of sophistication and firm size. Moore and Reichert (1983), who survey 298 Fortune 500 firms find that 86% of firms surveyed use time-adjusted capital budgeting techniques. Bierman (1993) finds that all 74 responding Fortune 100 companies use some form of discounting, and 93% calculate the weighted average cost of capital.…”
Section: Practice In the Fieldmentioning
confidence: 99%